The Effect of Pare (Momordica Charantia) L. Ethanol Extract on The Formation of Cataracts in Wistar White Rats - Nur Rahayuningsih; Desi Agni Mutia; Tita Nofianti (Jurnal Farmasi (Journal of Pharmacy), 2021)
Cataract is a clouding of the lens of the eye that reduces the amount of light entering and results in impaired vision. Cataracts remain the leading cause of visual impairment and blindness worldwide. Bitter melon fruit contain flavonoids and polyphenols which have antioxidant activities. Thirty of 9 days age wistar rats was divided into six group. Normal and negative group were given 2 ml/200 g BW rats 1% of PGA orally. Positive control was given 0,0009 g/200 g BW rat of vitamin C. Test group 1, 2, and 3 (were given 0,025 g/200 g BW rats; 0,051 g/200 g BW rats; and 0,1 g/200 g BW rats bitter melon fruit ethanol extract orally, respectivelly). All of the group except Normal were inducted with 0,25 mg/200 g BW rats sodium selenit subcutaneously. Treatment was given until the rat open the eyes for the first time (± 18 days). Eyes were observed macroscopic and microscopically in all group. The ethanol extract of bitter melon (Momordica charantia L.) has preventive activity against the formation of cataracts. The negative control group and dose I included in stage IV, positive control included in stage I, dose II included in stage III and dose III included in stage II. The most effective dose which prevent the formation of eye cataracts was 0,1 g/200 g BW rats bitter melon fruit (Momordica charantia L.) ethanol extract.Keywords : Cataract, Bitter melon fruit, flavonoids